Health and society in Chukotka: an overview - Dudarev, AA; Chupakhin, Valery; Odland, Jon Øyvind (International Journal of Circumpolar Health, 2013)
This study provides a historical overview of the changes in the socio-economic and health status of the population of Chukotka, from the Soviet to the post-Soviet period, with special attention paid to the circumstances of indigenous people. Past health studies in Chukotka are reviewed and key demographic and health indicator data presented. Since the 1990s, Chukotka’s population has shrunk to a third of its former size due to emigration of nonindigenous and mostly younger people, with a corresponding increase in the mortality rate due to aging of the population. However, the indigenous population has remained stable. Among the most important causes of mortality are injuries. The living conditions of indigenous people continue to be a cause of concern, beset by high rates of poverty, unemployment, alcoholism, suicide and a variety of infectious diseases, such as tuberculosis and sexually transmitted infections. The economy, general infrastructure and health care system of Chukotka have been considerably improved by the Abramovich administration in the 2000s.